Ownership Structure and Financial Performance of Listed Consumable Goods Companies in Nigeria - Akinleye, G.T.; Olaniyi , Adebusoye (Acta Universitatis Danubius. Œconomica, 2023)
The study examined effect of ownership structure on financial performance of listed consumable goods companies in Nigeria between 2013 and 2022. Specifically, the study examined the effect of managerial ownership and foreign ownership on return on assets of listed consumable goods companies in Nigeria. The study employed secondary source of data and the data were collated from financial reports of sampled 10 listed consumable goods companies. In bid to accomplish this, panel regression analysis was employed, having considered the fixed effect model as the most fitted data estimator, the result revealed that managerial ownership has a positive effect on return on assets with coefficient of (0.502224) and statistically significant (p=0.03057<0.05). Similarly, foreign ownership has positive effect on return on asset with coefficient of (0.383082) and statistically significant (p=0.04110<0.05). Based on the findings of this study, the study concluded that both managerial ownership and foreign ownership have positive effect on the financial performance of the selected consumable goods companies in Nigeria. The study therefore recommended that, the management of consumable goods companies should improve on their insider’s ownership